Cold storage promotes germination and colonization of arbuscular mycorrhizal fungal hyphae as propagules - Liu, Xiaodi; Ye, Guojian; Feng, Zengwei; Zhou, Yang; Qin, Yongqiang; Yao, Qing; Zhu, Honghui (Frontiers in Plant Science, 2024)
The inoculants of arbuscular mycorrhizal fungi (AMF) propagated by the in vitro culture system is important in scientific research; however, the long-term storage reduces the spore germination rate. The propagules of AMF consist of three components, including spores, hyphae and colonized root fragments. It is well known that cold storage can improve the germination rate of AMF spores, with limited investigations on the germination of other propagules. In this study, AMF inoculants were stored at 25°C or at 4°C (cold storage) to investigate the effect of cold storage on the propagule viability of the AMF Rhizophagus irregularis DAOM197198. The germination rate of propagules (spores, hyphae, root fragments) and their colonization ability were determined at 3 and 6 months after storage. The results showed that the spore germination rate remained unchanged after storage for 0 and 1 month at 25°C, but decreased rapidly after storage for 3 months. Furthermore, we investigated the hyphal germination rate for the first time. The germination rates of spores, hyphae and root fragments were significantly higher under cold storage compared to those at 25°C. Additionally, we classified the germ tubes of hypha into two types: long-type (L-type) and short type (S-type). The germination rate and the proportion of L-type germ tubes of hyphae significantly increased with cold storage time, which was conducive to colonization. The results of mycorrhizal colonization confirmed that cold storage significantly increased the colonization of hypha compared with 25°C treatment. Cold storage may break the dormancy of AMF propagules and activate related enzymes to promote the germination and colonization of propagules, which needs further investigation.